Augmented Reality in the Classroom—Mentor Teachers’ Attitudes and Technology Use - Corinne Wyss; Kerstin Bäuerlein (Virtual Worlds)
The education sector is becoming increasingly interested in augmented reality (AR) technology. Research has revealed that AR offers a multitude of benefits in supporting learning. Nevertheless, the implementation of AR in the classroom remains limited. As teachers play a pivotal role in the integration of AR in the classroom, it is essential to understand their perspectives to comprehend the factors hindering the widespread adoption of AR at schools. However, few studies have explored teacher attitudes towards integrating AR into educational practice. The present questionnaire study thus seeks to elucidate the perspectives of 158 mentor teachers in German-speaking Switzerland on the implementation of AR in the classroom. The findings suggest that although mentor teachers have a moderately positive attitude towards AR, they have only limited experience with the technology and appear to lack the requisite technical and pedagogical skills and resources. Furthermore, certain teacher characteristics impact the perception of AR as a useful tool and its integration into teaching practice. Teachers seem to require enhanced information, training, and support if augmented reality (AR) is to become a prevalent feature in schools in the future. To this end, further studies need to consider teacher characteristics in more detail.